2015
DOI: 10.2319/040315-225.1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects of skeletally anchored Forsus FRD EZ and Herbst appliances: A retrospective clinical study

Abstract: Although both appliances were successful in correcting the skeletal Class II malocclusion, the skeletally anchored Forsus FRD EZ appliance did so without protruding the mandibular incisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
57
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 31 publications
10
57
1
3
Order By: Relevance
“…In accordance with our results, Unal et al 12 and Celikoglu et al 13 also reported significant mandibular posterior rotation with a skeletally anchored Forsus appliance. In contrast, Aslan et al 11 reported nonsignificant changes in the mandibular plane angle with miniscrew-supported and conventional Forsus appliances.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In accordance with our results, Unal et al 12 and Celikoglu et al 13 also reported significant mandibular posterior rotation with a skeletally anchored Forsus appliance. In contrast, Aslan et al 11 reported nonsignificant changes in the mandibular plane angle with miniscrew-supported and conventional Forsus appliances.…”
Section: Discussionsupporting
confidence: 82%
“…Our results were in accordance with previous studies that have reported similar findings with Forsus appliances. 3,[6][7][8][9][12][13][14]16,17 In contrast, several studies have reported that the Forsus FRD had no significant effect on maxillary growth. 2,5,10,11,18 The effects of the Forsus FRD on mandibular growth were investigated by SNB and Co-Gn measurements.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations